Who possesses drug resistance genes in the aquatic environment?: sulfamethoxazole (SMX) resistance genes among the bacterial community in water environment of Metro-Manila, Philippines - Suzuki, Satoru; Ogo, Mitsuko; Miller, Todd W.; Shimizu, Akiko; Takada, Hideshige; Siringan, Maria Auxilia (Frontiers in Microbiology, 2013)
Recent evidence has shown that antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) are ubiquitous in natural environments, including sites considered pristine. To understand the origin of ARGs and their dynamics, we must first define their actual presence in the natural bacterial assemblage. Here we found varying distribution profiles of sul genes in “colony forming bacterial assemblages” and “natural bacterial assemblages.” Our monitoring for antibiotic contamination revealed that sulfamethoxazole (SMX) is a major contaminant in aquatic environments of Metro-Manila, which would have been derived from human and animal use, and subsequently decreased through the process of outflow from source to the sea. The SMX-resistant bacterial rate evaluated by the colony forming unit showed 10 to 86% of the total colony numbers showed higher rates from freshwater sites compared to marine sites. When sul genes were quantified by qPCR, colony-forming bacteria conveyed sul1 and sul2 genes in freshwater and seawater (10−5–10−2 copy/16S) but not sul3. Among the natural bacterial assemblage, all sul1, sul2, and sul3 were detected (10−5–10−3 copy/16S), whereas all sul genes were at an almost non-detectable level in the freshwater assemblage. This study suggests that sul1 and sul2 are main sul genes in culturable bacteria, whereas sul3 is conveyed by non-culturable bacteria in the sea. As a result marine bacteria possess sul1, sul2 and sul3 genes in the marine environment.